2022
DOI: 10.32942/osf.io/4p638
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shared neural transcriptomic patterns underlie the repeated evolution of mutualistic cleaning behavior in Labridae wrasses

Abstract: Despite the remarkable diversity of life forms on earth, evolutionary biologists have discovered numerous instances where even distantly related species share astonishing similarities in how they behave, look, and function. Given the importance of happenstance in evolution (e.g., random mutations, genetic drift, environmental stochasticity), it is often assumed that the mechanisms underlying such convergent phenotypes are distinct. Nevertheless, recent discoveries that the same pathways can underlie convergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…This could have been either owing to the available genetic variants differing ( sensu the mutation order hypothesis [ 51 53 ]), or because selection was less similar than thought. Although there are exciting examples of parallel gene expression changes underlying the parallel evolution of complex behavioural phenotypes [ 11 14 , 33 ], it seems that parallel phenotypic evolution often rests on only partly parallel genetic mechanisms [ 31 , 54 ], as is suggested by the data from the two limnetic populations here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could have been either owing to the available genetic variants differing ( sensu the mutation order hypothesis [ 51 53 ]), or because selection was less similar than thought. Although there are exciting examples of parallel gene expression changes underlying the parallel evolution of complex behavioural phenotypes [ 11 14 , 33 ], it seems that parallel phenotypic evolution often rests on only partly parallel genetic mechanisms [ 31 , 54 ], as is suggested by the data from the two limnetic populations here.…”
Section: Resultsmentioning
confidence: 99%
“…However, we know little about the cognitive and molecular mechanisms that underpin such decision-making or how these mechanisms vary across species [ 9 , 10 ]. Comparative transcriptomic studies, where constitutive gene expression profiles are systematically analysed across different populations, species and environments, have already provided important insights into the evolution of molecular mechanisms underlying various complex behaviours, such as learned vocalizations [ 11 ], mating systems [ 12 , 13 ], and cooperation [ 14 ]. Recent studies have also identified dynamic transcriptomic variation related to mate choice [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could have been either due to the available genetic variants differing ( sensu the mutation order hypothesis (Mani and Clarke 1997; Schluter 2009; Mendelson et al 2014)), or because selection was less similar than thought. Although there are exciting examples of parallel gene expression changes underlying parallel evolution of complex behavioral phenotypes (Pfenning et al 2014; Renn et al 2018; Young et al 2019; Jacobs et al 2020; Young et al 2022), it seems that parallel phenotypic evolution often rests on only partly parallel genetic mechanisms (Soria-Carrasco et al 2014; Bolnick et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…However, we know very little about the cognitive and molecular mechanisms that underpin such decision-making or how these mechanisms may vary across species and depend on ecological factors (DeAngelis and Hofmann 2020; Ryan 2021). Comparative transcriptomics, where gene expression profiles are systematically analyzed across different populations, species, and environments, have already provided important insights into the evolution of mechanisms underlying various complex behaviors, such as learned vocalizations (Pfenning et al 2014), mating systems (Renn et al 2018; Young et al 2019), and cooperation (Young et al 2022). Recent transcriptomic studies have also identified some genes that appear to be involved in female mate choice (Cummings et al 2008; Bloch et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Young et al 2022;Kang et al 2023). The former analysis was based on two telencephalic nodes of the Social Decision-Making Network, the medial (Dl; lateral part of the dorsal telencephalon) and the lateral pallium (area Dm; medial part of the dorsal telencephalon).…”
mentioning
confidence: 99%